2002
DOI: 10.1023/b:fish.0000021866.78048.45
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 18:4n-3 (stearidonic acid) and 20:4n-3 in salmonid cells in culture and inhibition of the production of prostaglandin F(PGF) from 20:4n-6 (arachidonic acid)

Abstract: Arachidonic acid (AA;) is the precursor of a range of highly biologically active derivatives, collectively termed eicosanoids, including prostaglandins, thromboxanes, leukotrienes and lipoxins, that act as autocrine hormones regulating many physiological processes including haemostasis, reproduction, immune and inflammatory responses. Eicosapentaenoic (EPA; 20:5n-3) and dihomo-γ-linolenic (20:3n-6) acids modulate eicosanoid metabolism by both inhibiting the conversion of AA to eicosanoids whilst simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Moreover, as a precursor of EPA, it is possible that eicosatetraenoic acid could more accurately reflect n‐3 PUFA status than EPA. Furthermore, like EPA and other long‐chain n‐3 PUFAs, C20:4n‐3 has been shown to have anti‐inflammatory effects by inhibiting the conversion of arachidonic acid to prostaglandins [18]. Similarly, like other n‐3 PUFAs, C20:4n‐3 is readily incorporated into various phospholipid species, which is consistent with the possible modulatory effects on eicosanoid metabolism.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, as a precursor of EPA, it is possible that eicosatetraenoic acid could more accurately reflect n‐3 PUFA status than EPA. Furthermore, like EPA and other long‐chain n‐3 PUFAs, C20:4n‐3 has been shown to have anti‐inflammatory effects by inhibiting the conversion of arachidonic acid to prostaglandins [18]. Similarly, like other n‐3 PUFAs, C20:4n‐3 is readily incorporated into various phospholipid species, which is consistent with the possible modulatory effects on eicosanoid metabolism.…”
Section: Discussionmentioning
confidence: 57%
“…In the latter case, this was demonstrated by using verified biological standards previously generated in transgenic Arabidopsis lines accumulating juniperonic acid (Figure S1; Sayanova et al ., ). Interestingly, ETA is often observed at low levels in fish oils and has been ascribed anti‐inflammatory activities similar to EPA (Ghioni et al ., ). Thus, ETA can be considered as an additional omega‐3 LC‐PUFA widely distributed in marine food webs.…”
Section: Resultsmentioning
confidence: 97%
“…In earlier studies with fish cell cultures, supplemental STA was readily elongated to 20:4n‐3 (Ghioni et al 2004), suggesting that EO may be a useful oil to include in novel dietary formulations for marine fish as it has the potential to increase tissue levels of both 20:4n‐3 and 20:3n‐6. This could have beneficial effects in modulating ARA metabolism in fish, particularly when being fed VO diets with reduced levels of EPA that would normally regulate ARA and eicosanoid metabolism.…”
Section: Introductionmentioning
confidence: 98%
“…Another naturally occurring C 20 HUFA that can be converted to eicosanoids and modulate eicosanoid metabolism in mammals is 20:4n‐3 (Oliw, Sprecher & Hamberg 1986a,b; Careaga and Sprecher 1987; Croset, Bordet & Lagarde 1999). Recently we showed that 20:4n‐3 decreased the conversion of ARA into prostaglandins (PGs) in fish, as demonstrated by the decreased levels of PGF 2α produced in trout macrophages supplemented with 20:4n‐3 and ARA compared with cells supplemented with ARA alone (Ghioni, Porter, Taylor & Tocher 2004). In addition, 20:4n‐3 was converted into eicosanoids in fish cells as indicated by the presence of Δ 17,18 12‐HETE, Δ 17,18 PGE 1 and Δ 17,18 PGF 1α in extracts from rainbow trout ( Oncorhynchus mykiss ) macrophages incubated with 20:4n‐3 (Ghioni et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation